Risk factors of mortality in patients with purple urine bag syndrome. (1st January 2019) - Su, Yu-Jang; Yang, Hsiu-Wu
Abstract: Aim: Purple urine bag syndrome (PUBS) is rarely seen in clinical practice. Several studies have reported that PUBS is relatively benign in its clinical course, but this study aimed to identify risk factors for mortality related to PUBS. Materials and methods: In a PubMed search from October 1980 to August 2016, using the search term "Purple urine bag syndrome (PUBS)", 106 articles (n = 174 cases) were identified. This study excluded 58 cases. Among them, 14 cases did not include information on patient sex and four cases did not include information on patient age. Thirty-seven cases did not report the white blood cell (WBC) count, shock, fever, or etiology. Three cases did not report patient survival. This study considered 116 PUBS cases. Chi-square tests were used to compare the survival and mortality groups. Results: In relative risk analysis, uremia (17.8), shock (14.4), diabetes (4.8), leukocytosis (1.1), and female sex (1.1) were significant risk factors for mortality after PUBS. However, it is possible that PUBS cases are under-reported worldwide. Conclusions: PUBS is a warning sign of a urinary tract infection, and it often follows a relatively benign clinical course. This study found that female sex, leukocytosis, shock at presentation, comorbidity with diabetes, and uremia are risk factors for mortality associated with PUBS.